2011
DOI: 10.1103/physreve.84.036405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser-plasma interactions on terahertz radiation from solid targets irradiated by ultrashort intense laser pulses

Abstract: Interactions of 100-fs laser pulses with solid targets at intensities of 10(18) W/cm(2) and resultant terahertz (THz) radiation are studied under different laser contrast ratio conditions. THz emission is measured in the specular reflection direction, which appears to decrease as the laser contrast ratio varies from 10(-8) to 10(-6). Correspondingly, the frequency spectra of the reflected light are observed changing from second harmonic dominant, three-halves harmonic dominant, to vanishing of both harmonics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…We can see the obvious 3/2 harmonic at 533 nm and relatively weak second harmonic at 400 nm. This is in good agreement with our previous experimental and theoretical results under this ASE contrast ratio condition [22]. At each THz radiation detection angle, at least 6 efficient shot data was recorded.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We can see the obvious 3/2 harmonic at 533 nm and relatively weak second harmonic at 400 nm. This is in good agreement with our previous experimental and theoretical results under this ASE contrast ratio condition [22]. At each THz radiation detection angle, at least 6 efficient shot data was recorded.…”
Section: Resultssupporting
confidence: 74%
“…In our recent work, we have obtained a THz energy as high as 50 μJ/sr per shot and discussed the effect of the laser contrast ratio 1) [22]. In this paper, we will present the measurement of the angular distribution of the THz radiation and discuss the THz generation mechanism.…”
Section: Introductionmentioning
confidence: 95%
“…3(a) show that this is the smaller possible scale length to observe 3x/2 in our conditions. It has to be noticed [22][23][24] that the intensity of the main pulse at that target position, namely I % 4.5Á10 17 Wcm À2 would be still enough to excite TPD provided a suitable plasma scale-length exists. Therefore, while the maximum X-ray yield appears to be a combined effect of both maximum intensities of main pulse and ASE, the vanishing of 3x/2 emission is mostly likely due to the lower plasma scale length.…”
Section: Experimental and Numerical Resultsmentioning
confidence: 99%
“…This requirement basically remains valid with ultra-short and ultra-intense pulses, but the higher laser intensities generally result in a significant reduction of the scale length needed for the growth of the TPD instability. [22][23][24][25] The formation of a pre-plasma can provide, before of the arrival of the main pulse, a scale length suitable for stimulated instabilities to grow. Veisz et al 26 reported the first measurements of 3x/2 emission in a long density scale-length plasma (L % 100/200 k 0 ) in the ultra-short pulse regime (100 fs).…”
Section: Introductionmentioning
confidence: 99%
“…Interesting researches are being carried out in laboratories around the world to develop tabletop sources of highly energetic charged particles and photons [5]. Recently, it has been found that intense laser-plasma interaction can also generate intense broadband terahertz (THz) pulses [6][7][8][9]. THz radiation is very useful for imaging and probing physical systems because of its nonionizing behavior, and also since it can pass through many materials that are opaque in the visible range.…”
mentioning
confidence: 99%